2015
DOI: 10.1007/s10495-015-1193-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic agent CPT-11 eliminates peritoneal resident macrophages by inducing apoptosis

Abstract: CPT-11 (Irinotecan) is a first-line chemotherapeutic agent in clinic, but it may induce side effects including diarrhea and enteritis in patients. The underlying mechanism of CPT-11's intestinal toxicity is unclear. Peritoneal resident macrophages have been reported to be important for the maintenance of intestinal homeostasis. In this study, we evaluated the cytotoxic effects of CPT-11 on mouse peritoneal resident macrophages. CPT-11 was administered intraperitoneally to mice and their peritoneal exudate cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…However, the numbers of SPMs were not significantly changed by CPT-11, despite their increased ratios within the CD11b + population (Figures 1 B,C). Together with previous studies ( 13 ), these results indicated that the resident peritoneal macrophages were rapidly depleted by i.p. CPT-11 treatment.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…However, the numbers of SPMs were not significantly changed by CPT-11, despite their increased ratios within the CD11b + population (Figures 1 B,C). Together with previous studies ( 13 ), these results indicated that the resident peritoneal macrophages were rapidly depleted by i.p. CPT-11 treatment.…”
Section: Resultssupporting
confidence: 89%
“…Although we have demonstrated that CPT-11 can deplete the resident peritoneal macrophages ( 13 ), the dynamic details underlying this process remain unknown. For example, could the resident peritoneal macrophages and B1 cells recover from CPT-11 treatment by self-renewal?…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations